Qur'anic Illiteracy Caused by Internet Addiction: Da'wah Challenges and Local Responses in Matondang Village, North Sumatra - Hamdan Daulay; Evi Septiani Tavip Hayati; Mohamad Hasan As'adi (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
The widespread use of social media in remote Matondang Village has created serious challenges for adolescents. This study aims to explore the challenges faced by Quranic teachers in preventing Qur’anic illiteracy among adolescents caused by internet media exposure in Matondang Village, North Sumatra. This study employed a qualitative research approach. The primary data were obtained from preachers and community leaders of Matondang village. Secondary data were obtained from library sources, including books, journal articles, research reports, government regulations, and newspapers relevant to the impact of social media and the moral crises affecting adolescents. Data collection techniques include observation, interviews and documentation. The results showed that juru dakwah plays an important role in delivering religious tausiyah among the younger generation. The da'wah movement is carried out in the form of recitation activities, activating the culture of reading the Qur'an and persuasive communication as an effort to foster morals. Recitation activities are carried out every Friday night and are guided by ustadz or ustadzah alternately as mentors, giving lectures and practicing reading the Qur'an. These activities contribute to strengthening adolescents’ moral character and preventing negative behaviour and Qur’anic illiteracy